Gender-specific distributional Effects of the Reforms of the Austrian Tax and Welfare System - Pechmann, Patrick (Momentum Quarterly, 2016)
This article investigates the distributional effects of the latest tax reforms in Austria. The period under review includes the reforms of 2004/05, 2009 and 2015/16. While most research focuses on the general aspect of the distribution of income, this paper extends the analyses to the effects on gender-specific income distribution caused by changes in the tax structure. Using current statistical methods, it can be concluded that these reforms generally had a positive influence on low and high levels of income alike. Lower incomes, where the share of women is larger, often have the highest relative income growth. However, men are more often represented in higher income groups and can profit through constant tax relief for top incomes. Further, a special analysis of the allowances, which reduce the taxable base for social security contributions as well as for income taxes, also disproportionally favour men. Hence, they even lead to a redistribution from women to men. Furthermore the study also demonstrates that occupational groups with a higher share of male workers are more favoured by the tax reforms.
Keywords: income-distribution; taxation; gender-budgeting; tax-reforms